The P2Y1 Receptor Is Normal in a Patient Presenting a Severe Deficiency of ADP-induced Platelet Aggregation - Léon, Catherine; Vial, Catherine; Gachet, Christian; Ohlmann, Philippe; Hechler, Béatrice; Cazenave, Jean-Pierre; Lecchi, Anna; Cattaneo, Marco (Thrombosis and Haemostasis, 1999)
ADP is a key stimulus inducing platelet shape change and aggregation, a rise in internal calcium and inhibition of adenylyl cyclase. These signaling pathways are thought to be activated by three independent receptors, but to date only the P2Y1 receptor responsible for calcium mobilization and the ionotropic P21 receptor have been identified. We report here the characteristics of the P2Y1 receptor in a patient presenting a selective deficiency of ADP-induced aggregation. Cloning of the P2Y1 gene revealed that the patient’s DNA and mRNA were normal. Pharmacological studies showed that the P2Y1 receptor was expressed and functional in patient’s platelets. Hence, the P2Y1 receptor is not the cause of the impaired ADP-induced platelet aggregation in this patient. The P21 mRNA was also found to be present and normal. These findings add evidence to previous observations suggesting that a third P2 receptor coupled to adenylyl cyclase may be involved in ADP-induced platelet aggregation.